Energy conversion strategies during 100 m sprinting - Ward-Smith, A. J. (Journal of Sports Sciences, 2001)
The aims of this study were to examine energy conversion strategies during 100 m sprinting and to determine whether there are opportunities for performance enhancement beyond the usual 'maximum effort throughout' strategy. The roles of aerodynamic drag and kinetic energy recovery on the overall whole-body energy balance are discussed. A mathematical model based on sprinting with maximum effort, converting chemical energy as rapidly as possible to mechanical energy, is used to calculate a reference performance. Subsequent calculations show the effect of inserting a period of constant-speed running on overall running time. The paper explores how the timing of entry into the second phase affects the overall running time. Overall, the calculations show that no benefits result from adopting a running strategy involving the insertion of a constant-speed phase; the analysis confirms that the strategy of running with maximum effort is the optimum. For a certain range of conditions, the insertion of a short period of constant-speed running has been shown to have a negligible effect on overall running time. For elite male athletes, the constant-speed phase may be entered between 55 and 60 m from the start line, while for elite female athletes the corresponding values are between 46 and 53 m from the start. J Sports Sci 2001 Sep;19(9):701-10